An integrated framework for reducing precast fabrication inventory - Ko, Chien-Ho (Journal of Civil Engineering and Management, 2010)
Precast fabricators strive for business success on delivering products on time. To achieve this goal, fabricators start fabrication once they receive design information. However, this practice results in finished goods inventory which is regarded as waste. The objective of this study is to develop a framework for precast fabricators to reduce the inventory. The framework consists of three components. The first time buffer evaluation is used to avoid fabricators losing capacity by considering demand variability. The second component, due date adjustment, shifts production curve closer to erection dates to reduce inventory. The third scheduling component arranges production sequences to achieve multi-objectives using genetic algorithms. One real case is experimented to demonstrate the effectiveness of the proposed framework. The application results show that the developed framework can reduce the level of finished goods inventory without changing production resources.First Published Online: 10 Feb 2011